The Innocent Man : Murder and Injustice in a Small Town - Grisham, John (London Century, 2006)
In the town of Ada, Oklahoma, Ron Williamson was going to be the next Mickey Mantle. But on his way to the Big Leagues, Ron stumbled, his dreams broken by drinking, drugs, and women. Then, on a winter night in 1982, not far from Ron$1 (Bs home, a young cocktail waitress named Debra Sue Carter was savagely murdered. The investigation led nowhere. Until, on the flimsiest evidence, it led to Ron Williamson. The washed-up small-town hero was charged, tried, and sentenced to death$1 (Bin a trial littered with lying witnesses and tainted evidence that would shatter a man$1 (Bs already broken life$1! =(Band let a true killer go free.s
Include Illustrations.
English Fiction.
Keywords: Trials (Murder) -- Judicial error -- Williamson, Ronald Keith, 1953-2004 -- Oklahoma -- Capital punishment